ISSUES RELATED TO THE ROLE OF INFORMATION TECHNOLOGY IN THE DEVELOPMENT OF CONSTRUCTION AND THE IMPORTANCE OF FOREIGN LANGUAGES IN STUDYING FOREIGN EXPERIENCES AND THE PREPARATION OF TEXTBOOKS IN COOPERATION - Hushboqova Prayer Ram qizi; Shohista Hdoyatillo qizi (Galaxy International Interdisciplinary Research Journal, 2023)
This article details the role of information technology in the development of construction and the importance of foreign languages in studying foreign experiences and the issues of preparing textbooks in cooperation, the widespread use of pedagogical and information technology, and the development and prospects of information technology today, when information communication technologies are rapidly developing